Effect of Dietary Fiber and Metabolites on Mast Cell Activation and Mast Cell-Associated Diseases - Folkerts, Jelle; Stadhouders, Ralph; Redegeld, Frank A.; Tam, See-Ying; Hendriks, Rudi W.; Galli, Stephen J.; Maurer, Marcus (Frontiers in Immunology, 2018)
Many mast cell-associated diseases, including allergies and asthma, have seen a strong increase in prevalence during the past decades, especially in Western(ized) countries. It has been suggested that a Western diet may contribute to the prevalence and manifestation of allergies and asthma through reduced intake of dietary fiber and the subsequent production of their metabolites. Indeed, dietary fiber and its metabolites have been shown to positively influence the development of immune disorders via changes in microbiota composition and the regulation of B- and T-cell activation. However, the effects of these dietary components on the activation of mast cells, key effector cells of the inflammatory response in allergies and asthma, remain poorly characterized. Due to their location in the gut and vascularized tissues, mast cells are exposed to high concentrations of dietary fiber and/or its metabolites. Here, we provide a focused overview of current findings regarding the direct effects of dietary fiber and its various metabolites on the regulation of mast cell activity and the pathophysiology of mast cell-associated diseases.